The Role of Structure in the Biology of Interferon Signaling - Walter, Mark R. (Frontiers in Immunology, 2020)
Interferons (IFNs) are a family of cytokines with the unique ability to induce cell intrinsic programs that enhance resistance to viral infection. Induction of an antiviral state at the cell, tissue, organ, and organismal level is performed by three distinct IFN families, designated as Type-I, Type-II, and Type-III IFNs. Overall, there are 21 human IFNs, (16 type-I, 12 IFNαs, IFNβ, IFNε, IFNκ, and IFNω ; 1 type-II, IFNγ; and 4 type-III, IFNλ1, IFNλ2, IFNλ3, and IFNλ4), that induce pleotropic cellular activities essential for innate and adaptive immune responses against virus and other pathogens. IFN signaling is initiated by binding to distinct heterodimeric receptor complexes. The three-dimensional structures of the type-I (IFNα/IFNAR1/ IFNAR2), type-II (IFNγ/IFNGR1/IFNGR2) and type-III (IFNλ3/IFNλR1/ IL10R2) signaling complexes have been determined. Here, we highlight similar and unique features of the IFNs, their cell surface complexes, and discuss their role in inducing downstream IFN signaling responses.